Comments on Responses to ‘What is Mother Earth?’ - Gill, Sam (Journal for the Study of Religion, Nature and Culture, 2024)
Sam Gill responds to his interlocutors concerning the concept of Mother Earth and its employment in indigenous studies and beyond.